Docs team-based professional development make a difference? A longitudinal investigation of teacher learning through curriculum design (Journal of Educational Management, 2014)
While a growing body of literature documents teachers' involvement in curriculum design, this study further assesses curriculum design among teacher teams for instructional improvement and teacher development in some higher institutions in Ghana. Six teams of teachers were studied over a three year period as they redesigned their courses to commensurate with contemporary workplace skill demands and improve instruction. Results from data collected through interviews, questionnaires, observation, and field notes showed teacher professional development gains, especially due to shared knowledge and collective efforts to pursue up-to-date information from relevant sources to develop the curriculum. The classroom implementation of the redesigned courses revealed industry-relevant lesson experiences for students. It was concluded that participation in professional development-focused curriculum design can impact teacher learning and practice. This study emphasizes the importance of teacher collaboration and marks a first step toward identifying how learning processes are encouraged and knowledge is constructed in design teams.